False positive rate of serum markers for Down syndrome screening: does transportation have any effect? - Sirichotiyakul S. (2014)
Objective: To determine the false positive rate of serum markers for Down syndrome screening caused by transportation by analyzing samples sent from different hospitals at various distances. Material and Method: The database of serum markers between March 2008 and August 2010 was retrieved from Maternal- Fetal the Medicine unit, Department of Obstetrics and Gynecology, Faculty of Medicine, Chiang Mai University. The tests were performed using Delfia Xpress system. The cut off value for positive test result was 1 in 250. Result: Two thousand six hundred thirty one samples from hospitals located at various distances ranging from 0 to 449 km were assessed. The overall positive results were 6.1%, ranging from 5.6% among the hospitals near the laboratory to 15.4% among the hospitals far away from the laboratory (p-value < 0.001). The samples from the remote hospitals had significantly higher levels of free beta hCG than those from nearby hospitals (p-value = 0.003). Conclusion: The samples transported from the hospitals far from the laboratory need better storage and shipping procedure to avoid high false positive rate, which leads to unnecessary invasive prenatal diagnosis procedure.